Graphene and 2d-Like Nanomaterials: Different Biofunctionalization Pathways for Electrochemical Biosensor Development - Tasca-Gottardo, F; Tasca-Gottardo, F (Elsevier Inc., 2018)
In the last decades, nanotechnology has played a key role in the electrochemical biosensor development based on the mediated and direct electrochemical communication between the biorecognition elements and the electrode surface. In particular, graphene and 2D-like nanomaterials (e.g., boron nitride nanosheets, graphitic carbon nitride (g-C3N4) nanosheets, and various transition metal dichalcogenides) have attracted an increasing interest due to their peculiar properties such as high specific surface area and the ease of biofunctionalization. Moreover, in the last few years, the successful integration of graphene and 2D-like nanomaterials with other nanomaterials such as metal nanoparticles, metal oxides, or quantum dots has dramatically increased the opportunities to develop novel electrochemical biosensors with highly enhanced performances, mainly due to the synergistic effects.In this chapter, we would like to give the state of art of graphene and 2D-like nanomaterials employment for electrochemical biosensors development, by critically discussing the advantages and drawbacks. Successively, the discussion should be separately addressed to three different cases: (1) redox enzyme immobilization, (2) antibody immobilization, and (3) DNA/aptamer immobilization. Finally, we should critically define for which cases graphene and 2D-like nanomaterials are the most suitable electrochemical platform, within some conclusion remarks and future perspectives of both kinds of nanomaterials. © 2018 Elsevier Inc. All rights reserved.